The relation between lignin sequence and its 3D structure - Rawal, Takat B.; Zahran, Mai; Dhital, Brittiny; Akbilgic, Oguz; Petridis, Loukas (Biochimica et biophysica acta. General subjects, 2020)
Lignin, the second most abundant biopolymer on earth, plays a major structural role in plants, conferring mechanical strength and regulating water conduction. Understanding the three-dimensional structure of lignin is important for fundamental reasons as well as engineering plants towards lignin valorization. Lignin lacks a specific primary sequence, making its average chemical composition the focus of most recent studies. However, it remains unclear whether the 3D structure of lignin molecules depends on their sequence. We performed all-atom molecular dynamics simulation of three S/G-lignin molecules with the same average composition but different sequence. A detailed statistical analysis of the radius of gyration and relative shape anisotropy reveals that the lignin sequence has no statistically significant effect on the global three-dimensional structure. We found however, that homopolymers of C-lignin with the same molecular weight have smaller radii of gyration than S/G-lignin. We attribute this to lower hydroxyl content of C-lignin, which makes it more compact and rigid. The 3D structure of lignin is influenced by the overall content of monomeric units and interunit linkages and not by its precise primary sequence. Lignin is assumed to not have a well-defined primary structure. The results presented here demonstrate there are no significant differences in the global 3D structure of lignin molecules with the same average composition but different primary sequence. •Lignin does not have a well-defined primary structure or sequence.•The radii of gyration of models of lignin with different sequence but the same average composition are statistically similar.•C-lignin, because of its lower hydroxyl content, has smaller size than S/G-lignin with the same molecular weight.